Taxonomic and nomenclatural notes on freshwater Gastrotricha - Balsamo, Maria; D’hondt, Jean-Loup; Pierboni, Lara; Grilli, Paolo (Zootaxa, 2009)
Some taxonomic and nomenclatural remarks concerning freshwater species of Gastrotricha Chaetonotida are presented. In the family Chaetonotidae, the subgenus Chaetonotus (Hystricochaetonotus) is synonimized with the subgenus C. (Chaetonotus sensu stricto). The genus Lepidochaetus is moved to a subgeneric rank into the genus Chaetonotus, and the subgenus Nudichaetonotus Schwank, 1990 is synonymized with C. (Lepidochaetus). Chaetonotus (Lepidochaetus) brasilianus is proposed as a replacement name for Chaetonotus brasilense Kisielewski, 1991, which has become a secondary junior homonym of Chaetonotus brasiliensis Schwank, 1990. Emended diagnoses of the genus Chaetonotus and of the subgenera C. (Chaetonotus sensu stricto), and Chaetonotus (Lepidochaetus) are given. The 3 subgenera of the genus Ichthydium introduced by Schwank (1990) have not been introduced in the present list. In the family Dasydytidae, the subgenus Dasydytes (Setodytes) is synonymized with the genus Setopus. Six new species by Schwank (1990) (Aspidiophorus ontarionensis, Chaetonotus (C.) furculatus, Chaetonotus (Zonochaeta) annae, Ichthydium malleum, Lepidodermella forficulata and Dasydytes (Setodytes) lemnicola) are nomina nuda. An updated list of the reliable world freshwater species of Gastrotricha is reported.